Genetic control of root/shoot biomass partitioning in barley seedlings - Cabeza, Alejandra; Casas, Ana M.; Larruy, Beatriz; Costar, María Asunción; Martínez, Vanesa; Contreras-Moreira, Bruno; Igartua, Ernesto (Frontiers in Plant Science, 2024)
The process of allocating resources to different plant organs in the early stage of development can affect their adaptation to drought conditions, by influencing water uptake, transpiration, photosynthesis and carbon storage. Early barley development can affect the response to drought conditions and mitigate yield losses. A distinct behavior of biomass partitioning between two Spanish barley landraces (SBCC073 and SBCC146) was observed in a previous rhizotron experiment. A RIL population of circa 200 lines, derived from the cross of those lines was advanced using speed breeding. We devised an experiment to test if seedling biomass partitioning was under genetic control, growing the seedlings in pots filled with silica sand, in a growth chamber under controlled conditions. After one week, shoot and root were separated, oven-dried and weighted. There were genotypic differences for shoot dry weight, root dry weight and root to shoot ratio. The population was genotyped with a commercial 15k SNP chip and a genetic map was constructed with 1353 SNP markers. A QTL analysis revealed no QTL for shoot or root dry weight. However, a clear single QTL for biomass partitioning (RatioRS) was found, in the long arm of chromosome 5H. Exploring the high confidence genes in the region surrounding the QTL peak, five genes with missense mutations between SBCC146 and SBCC073, and differential expression in roots compared to other organs, were identified. We provide evidence of five promising candidate genes with a role in biomass partitioning that deserve further research.